DEVELOPMENT OF AN INTEGRATED TOURISM MANAGEMENT MODEL IN THE CORAL REEF TOURISM CONSERVATION AREA IN THE OLELE MARINE PARK DESTINATION - Mega Deza Tahta Rahmawati,; Fauzia Zees,; Amelya Mustamu,; Hasim, Hasim (Journal of Innovation Research and Knowledge, 2024)
Olele Marine Park is a marine park and marine tourism area located in Sulawesi. Olele Marine Park has unique beautiful underwater views in Gorontalo Bay (Tomini Bay). This area has potential natural resources that can be used for tourism and capture fisheries activities. However, the utilization of these two activities has not been regulated and managed optimally. The existence of these two potential activity sectors is a comparative advantage for Bone Bolango Regency to increase the economic value of Bone Bolango Regency. So there is a need for a tourism-fisheries development strategy through a SWOT analysis, namely to determine a development strategy for the Olele area conservation area. Based on the results of the analysis, the development strategy that can be carried out is a strategy that focuses on exploiting existing opportunities (opportunities) by using or optimizing strengths owned (strength)